About Two Types Of Universalism In The Musical Instruments Of The Kazakhs - Utegalieva, Saule; Alsaitova, Raushan; Mykyshev, Talgat; Slushash Ongarbayeva, Maksat Medeybek, (Opción, 2019)
The aim of the study is to investigate common features and differences between musical cultures of nomadic and settled Turks in Kazakhstan via comparative qualitative research methods. As a result, Timbre-register variation is actively used in dombra music. The compositional form of the kui - buyn (link) and with using transposition - suggests a register differentiation of the musical space. In conclusion, the timbre-register principle of development should be taken into account in the analysis of instrumental samples (dombra kui –tokpe and shertpe) and vocal-instrumental music not only of the Kazakhs, but also of other Turkic peoples.